Erratum: BELOKOBYLSKIJ, S.A., TANG, P., HE, J.H. & CHEN, X.X. (2012) The genus Doryctes Haliday, 1836 (Hymenoptera: Braconidae, Doryctinae) in China. Zootaxa, 3226, 46–60. - Belokobylskij, S. A.; Tang, P.; He, J. H.; Chen, X. X. (Zootaxa, 2012)
(Erratum)